Oxygen Reduction by Amide-Ligated Cobalt Complexes: Effect of Hydrogen Bond Acceptor - Zahra Aghaei; Adedamola A. Opalade; Victor W. Day; Timothy A. Jackson (Molecules)
The ability of earth-abundant metals to serve as catalysts for the oxygen reduction reaction is of increasing importance given the prominence of this reaction in several emerging technologies. It is now recognized that both the primary and secondary coordination environments of these catalysts can be modulated to optimize their performance. In this present work, we describe two CoII complexes [CoII(PaPy2Q)](OTf) (1) and [CoII(PaPy2N)](OTf) (2) that catalyze chemical and electrochemical dioxygen reduction. Both 1 and 2 contain CoII centers in a N5− coordination environment, but 2 has a naphthyridine group that places a nitrogen atom in the secondary coordination sphere. Solid-state X-ray crystallography and solution-state spectroscopic measurements reveal that, apart from this second-sphere nitrogen in 2, complexes 1 and 2 have essentially identical properties. Despite these similarities, 2 performs the chemical reduction of dioxygen ~10-fold more rapidly than 1. In addition, 2 has an enhanced performance in the electrochemical reduction of dioxygen compared to 1. Both complexes yield a significant amount of H2O2 in the chemical reduction of dioxygen (>25%). The enhanced catalytic performance of 2 is attributed to the presence of the second-sphere nitrogen atom, which might enable the efficient protonation of cobalt–oxygen intermediates formed during turnover.